CONDUCTING AUDITS IN PUBLIC ORGANIZATIONS: PROCEDURES AND BEST PRACTICES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Auditing in public organizations is essential for ensuring accountability, transparency, and efficient resource utilization. This article outlines the procedures for conducting audits in public organizations, emphasizing planning, execution, and reporting stages. It also highlights the importance of adhering to established frameworks and best practices to achieve reliable and actionable outcomes.